Slow-Growing Early Adenocarcinoma Arising from Traditional Serrated Adenoma in the Duodenum - Park, Yoon Kyoo; Jeong, Woo Jin; Cheon, Gab Jin (Case reports in gastroenterology, 2016)
Serrated polyps are classified into 3 distinct types: hyperplastic polyp, sessile serrated adenoma, or transitional serrated adenoma. A serrated adenoma is a precursor lesion for colorectal carcinoma. Serrated polyps are commonly found in the colorectum but have rarely been described in other parts of the gastrointestinal tract. Serrated adenomas in the small intestine may represent aggressive lesions with high malignant potential, according to some reports. A 66-year-old man with no significant medical history underwent esophagogastroduodenoscopy (EGD) for general examination. He had a 1-cm sized, Yamada type IV polyp, with focal white patch in the second portion of the duodenum. The biopsy result revealed gastric metaplasia and chronic inflammation. He wanted regular follow -up examinations. The follow-up EGDs were done every year. There were no changes in the shape and size of the polyp. The pathologic findings were unchanged. Then, he underwent EGD for general medical check-up again 5 years after the first detection. The size of the polyp was slightly increased. The biopsy result revealed serrated polyp, unclassified. Endoscopic mucosal resection was done. The pathologic result revealed a 0.8 × 0.5-cm sized, well differentiated tubular adenocarcinoma. Carcinomas are multifocally spread on the traditional serrated adenoma, and the proportion of the adenocarcinoma component is approximately 50%. The tumor had invaded the lamina propria but confined to the mucosa. The resection margins were negative, and no lymphovascular invasion or perineural invasion was seen. Abdominal pelvic computed tomography and positron emission tomography showed no other solid organ involvement or metastasis. Surveillance follow-up EGDs were done after 3 months and 1 year. There was no evidence of recurrence.